2016
DOI: 10.1002/cbf.3199
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain‐induced changes in MAP kinase phosphorylation in primary culture of rat cerebellar cells

Abstract: Cardiotonic steroid (CTS) ouabain is a well-established inhibitor of Na,K-ATPase capable of inducing signalling processes including changes in the activity of the mitogen activated protein kinases (MAPK) in various cell types. With increasing evidence of endogenous CTS in the blood and cerebrospinal fluid, it is of particular interest to study ouabain-induced signalling in neurons, especially the activation of MAPK, because they are the key kinases activated in response to extracellular signals and regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…The animal experiments were approved by the Bioethics Committee of the Faculty of Biology, Lomonosov Moscow State University (#82-O). Cerebellum was isolated from 7- to 8-day-old rat pups under sterile conditions as described previously [33]. Cerebellum cells were dissociated with 0.25% Trypsin-EDTA (Paneco) for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The animal experiments were approved by the Bioethics Committee of the Faculty of Biology, Lomonosov Moscow State University (#82-O). Cerebellum was isolated from 7- to 8-day-old rat pups under sterile conditions as described previously [33]. Cerebellum cells were dissociated with 0.25% Trypsin-EDTA (Paneco) for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that it is an integrated component of a hypothalamic renin-angiotensin-aldosterone system (RAAS) and also plays an important role in regulation of systemic Blood Pressure (BP) [ 37 , 40 , 56 ]. The relation between the central and peripheral RAASes with central and peripheral EO is still not completely understood [ 55 ], but it was discovered that EO-induced signaling in neurons had positive and direct consequences on rat brain in terms of brain cells survival [ 57 ]. Similarly, in mouse models, the reduction of endogenous steroids seems to have a protective effect on oxidative stress for CNS [ 58 ].…”
Section: The Correlation Between Endogenous Ouabain and Organ Damamentioning
confidence: 99%
“…Recent studies have demonstrated that α-synuclein 12 and β-amyloid 13 oligomers can inhibit Na,K-ATPase function, which may be one of the mechanisms underlying the relationship between Na,K-ATPase function and neurodegenerative processes. CTS ouabain is known to activate several signaling cascades in neurons, such as MAPK 14,15 , Akt 16 , PKC 17 , etc. Several studies have demonstrated that ouabain can modulate the function of the dopaminergic system by binding to Na,K-ATPase that functionally interacts with dopamine receptors 18 .…”
Section: Introductionmentioning
confidence: 99%